PENDIDIKAN KARAKTER SEBAGAI INSTRUCTIONAL EFFECT DAN NURTURANT EFFECT - nasrullah nasrullah (Prodi PAI STIT Sunan Giri Bima, 2022)
The purpose of this paper is to examine the importance of character education applied in educational institutions. The character education planting program launched by the government to be implemented through learning in schools prepared by teachers with reference to several components, namely; learning activity strategies that contain good character values ​​in students and the development of school culture that reflects good character. This will affect student outcomes, either partially or completely through learning in the form of knowledge and skills (instructional effect), it also still takes several meetings of subsequent teaching and learning events to further strengthen the results, why the results are called accompaniment impacts. The nurturing effect is in the form of results that are not directly measured and are not certain to be achieved at the end of a teaching and learning event meeting. Outcomes can be in the form of: (1) attitudes and values; (2) the results where students become modeling (can imitate), contagion (infected), osmosis (infiltrated) about the knowledge, skills, and attitudes of learning conditions, both programmed by the teacher and not programmed by the teacher. Keyword: Character Education, Instructional Effect, Nurturnt Effect